COVERINGS AND IDENTITIES: A SEMIOTIC REFLECTION ON ENSOR’S MASKS - Vivian Mendes Lopes (Cadernos de Letras da UFF, 2015)
This paper discusses the role of the mask in Ensor’s paintings, attending to how identity – as an element which is concealed and (re)construed by this figure – integrates the discourse structure where it is presented. The discussion is situated within the semiotics of A. J. Greimas and applies a semiotic model of identity (LANDOWSKI, 2002) to the analysis of the painting The Intrigue.